Photo splitting of bio-polyols and sugars to methanol and syngas - Min Wang (Nature Portfolio, 2020)
Methanol and syngas are important fuels and chemicals, which are presently produced from fossil resources. Here, the authors report the conversion of biomass-derived polyols and sugars into methanol and syngas via UV light irradiation under room temperature.